The Sound of Music - Wise, Robert (New Manila, Quezon City : Viva Video, 1999)
The Sound of Music, the most popular movie musical of all time, is a heartwarming, inspirational and true story based on the lives of the Trapp Family Singers, JULIE ANDREWS is Maria, a spirited, young Austrian woman studying to take her religious vows. Suspecting that Maria's true calling may lie outside the convent, the Mother Superior arranges for her to leave the convent and become governess to the children of the autocratic widower, Baron Von Trapp. Bringing warmth and music to the strict household of the reserved former naval captain, Maria soon wins over the children, and finally the Baron as well, in a gorgeously rendered romance. Richard Rodger's soaring, supple melodies and Oscar Hammerstein's joyful, inspirational lyrics are seamlessly joined in some of the world's best-loved son: "Do-Re-Mi," "Edelweiss" and many more.